The analysis and estimation of vibration fatigue for pipe fitting in aviation hydraulic system. (November 2019) - Zhang, Fuli; Yuan, Zhaohui; Zhang, Fuzhi; Liang, Na
Abstract: In aviation hydraulic systems, the pipe always operates under vibration, high pressure and variable temperature conditions, which leads to pipe fatigue or even hydraulic system failure. Therefore, this paper proposes a method to analyze and evaluate the fatigue properties of pipe fittings. Firstly, based on the D'Alembert principle and force analysis, the forced vibration model of the pipe is established. Thermal stress is obtained by using the temperature field model and the thermal stress function. Furthermore, the coupled stress model of the pipe is built by the superposition principle. Secondly, the fatigue damage evolution model of the pipe fittings is established by using the fatigue damage mechanics and the coupled stress model. Finally, the above model was validated based on the bending fatigue platform and software COMSOL. The studies concluded that the experimental value of fatigue life is close to the theoretical value. Analysis and estimation models are effective. The stress is concentrated at the fixed end and distributed in the axial direction. As the stress increases, the fatigue life is shortened. The frequency change has little effect on fatigue life compared to pressure. The effect of temperature on fatigue is minimal. These studies provide a theoretical basis for the safety of hydraulic systems. Highlights: The combined stress of the pipe fitting is obtained by the multi-field coupling model. Fatigue estimation of pipe fittings is established by the stress model and damage mechanics. The bending vibration platform and measurement system are designed and constructed. The stress-strain and fatigue characteristics of pipe fitting are further analyzed and studied.